A study on corrosion behavior of mild steel in Granulated Blast Furnace (GBFS) fly ash geopolmer - Siti Farahnabilah Muhd Amli (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
This research presents the corrosion behavior of mild steel embedded in geopolymer paste that produced by the reaction of fly ash and slag with an alkaline activators (NaOH molarity of 12 M, Na2SiO3/NaOH ratio of 2.5).